Linguistic landscape at Yogyakarta’s senior high schools in multilingual context: Patterns and representation - Andriyanti, Erna (Universitas Pendidikan Indonesia, 2019)
The study of linguistic landscape as a new approach to multilingualism has not been much explored within the Indonesian context. With regard to its significance to reveal various aspects of language use in education, this paper focuses on sign patterns in school linguistic landscape and what they represent in term of language situation in multilingual context. The data consist of 890 signs collected from five senior high schools in Yogyakarta. Based on the number and kinds of languages used, the data were categorised into their lingual patterns. The language situation was interpreted based on the main functions of language as a means of communication and representation. The findings of this research reveal three lingual patterns: monolingual, bilingual, and multilingual signs, which are ordered from the most to the least frequency. The monolingual and bilingual signs were found in all five schools while the multilingual ones in three schools. Bahasa Indonesia, English, and Arabic were found in all three patterns. Javanese and French were used in monolingual and multilingual patterns. Latin and Sanskrit were found only in monolingual pattern. As a means of communication and representation, the signage is both informative and symbolic. The studied school linguistic landscape reflects which languages are used and locally relevant to the school environments and how they are positioned. Bahasa Indonesia is dominant while Javanese is marginalised. The use of English in the school signs is frequent but indicates the sign makers’ less capability of the language. The use of Arabic is related to schools’ Islamic identity. Javanese is used as a cultural symbol. Due to its importance, the existing multilingualism at Yogyakarta’s schools should be maintained and efforts to achieve its balanced proportion need to be done.